HIPONATREMIA PADA SEORANG PENDERITA DENGAN KECURIGAAN INSUFISIENSI ADRENAL - Sri Yenny, Luh Gede; Gotera, Wira (journal of internal medicine; Vol. 8, No. 3 September 2007, 2012)
Hyponatremia is defined as a decrease in the serum sodium concentration to a level below 135 mmol per liter. Hyponatremia can be associated with low, normal, or high tonicity. One cause of hyponatremia is adrenal insufficiency. Serum sodium concentration is regulated by stimulation of thirst, secretion of ADH, feedback mechanisms of the renin-angiotensin-aldosterone system, and variations in renal handling of filtered sodium. Increases in serum osmolarity above the normal range (280-300 mOsm/kg) stimulate hypothalamic osmoreceptors, which, in turn, cause an increase in thirst and in circulating levels of ADH. ADH increases free water reabsorption from the urine, yielding urine of low volume and relatively high osmolarity and, as a result, returning serum osmolarity to normal. Aldosterone, synthesized by the adrenal cortex, is regulated primarily by serum potassium but also is released in response to hypovolemia through the renin-angiotensin-aldosterone axis. Aldosterone causes absorption of sodium at the distal renal tubule. In this report, patient is male, 64 years old, with probable adrenal insufficiency. Patient have very low respond to sodium teraphy. The sodium level increased and have good respond after corticosteroid teraphy. Patient have low level of cortisol serum (18,60 ?/dl) in critically ill condition. The possibility of adrenal insufficiency is of crucial importance in critically ill patients. If the diagnosis is missed, the patient will probably die. In such patients, a blood sample for the measurement of plasma cortisol and corticotropin should be obtained, a short corticotropin test (see below) should be performed, and immediate high-dose cortisol therapy should be considered or instituted. A plasma cortisol value in the normal range does not rule out adrenal insufficiency in an acutely ill patient. On the basis of a recent study of plasma cortisol concentrations in patients with sepsis or trauma, a plasma cortisol value of more than 25 ?g per deciliter in a patient requiring intensive care probably rules out adrenal insufficiency, but a safe cutoff value is unknown.
Keywords: hyponatremia, adrenal insufficiency